Чисті першопорядкові квазіaрні логіки з предикатами рівності - Нікітченко, М.С.; Шкільняк, C.С. (Проблеми програмування, 2017)
Вивчаються чистi першопорядковi квазіарні логіки однозначних та неоднозначних часткових предикатів. Основна увага приділена таким логікам із спеціальними предикатами рівності. Виділено чистi першопорядковi логіки з предикатами слабкої рівності та з предикатами строгої рівності. Описано мови та семантичні моделі цих логік, досліджено їх семантичні властивості, зокрема, властивості, пов’язані з предикатами рівності. Наведено властивості відношень логічного наслідку для множин формул. На базі цих властивостей для чистих першопорядкових логік з предикатами рівності побудовано низку числень секвенційного типу, для них доведено теореми коректності та повноти. Изучаются чистые первопорядковые логики однозначных и неоднозначных квазиарных предикатов. Эти логики являются программно-ориентированными логическими формализмами, отображающими такие свойства программ как частичность, недетерминизм, нефиксированную арность. Основное внимание уделено логикам со специальными предикатами равенства. Выделены чистые первопорядковые логики с предикатами слабого равенства и с предикатами строгого равенства. Описаны языки и семантические модели этих логик, исследованы их семантические свойства, в частности, свойства, связанные с предикатами равенства. Указаны свойства отношений логического следствия для множеств формул. На основе этих свойств для чистых первопорядковых логик с предикатами равенства построен ряд исчислений секвенциального типа, для них доказаны теоремы корректности и полноты. Logics of quasiary predicates are program-oriented logics which aim to reflect such program properties as partiality, non-determinism, and non-fixed arity. In the paper, program-oriented logical formalisms – pure first-order logics of partial deterministic and non-deterministic predicates – are studied. The main attention is paid to logics with special equality relations. Logics with weak equality and strong equality are defined, their properties are investigated. Languages of such logics and their interpetations are described. The following classes of interpretations (semantics) are identified: partial deterministic, non-deterministic, total deterministic, and total non-deterministic interpetations. Semantic properties of the proposed logics are investigated. Special attention is paid to consequence relations for sets of formulas. Based on the properties of these relations a number of calculi of sequent type is proposed. Basic rules of these calculi and corresponding closedness conditions are formulated; the procedure of sequent tree construction is described. For the proposed calculi correctness and completeness theorems are proved. The proof of completeness is based on the construction of countermodel for an unclosed path in the sequent tree.